ANALISIS PENGUASAAN KATA BANTU â€œLEâ€ DAN â€œGUOâ€ PADA MAHASISWA UNIVERSITAS TANJUNGPURA PROGRAM STUDI MANDARIN - Kurniawan, Rico; Thamrin, Lily; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstrackâ€œLeâ€ and â€œGuoâ€ are the examples of auxiliary words frequently appeared in mandarin language, and also an important point as well as the difficult point in the learning of mandarin language. In studying process, the frequency of the occurence of both words is quite high.The aim of this research is to know the differences and the similarities of the words â€œLeâ€ and â€œGuoâ€ and also to know the understanding condition of the students of University of Tanjungpura Chinese Language Major Batch 2016 about â€œLeâ€ and â€œGuoâ€. This research used literature study and also used the test method to test the understanding of the students of University of Tanjungpura Chinese Language Major Batch 2016. The test results indicate that the total percentages of the understanding of studentsâ€™ accuracy about â€œLeâ€ and â€œGuoâ€ are 68,75% and 72%. In conclusion, the results show the positive attitude towards the studentsâ€™ mastery in the use of the words â€œLeâ€ and â€œGuoâ€.Keywords : â€œLeâ€ and â€œGuoâ€, the condition of studentâ€™s understanding